Small-angle X-ray scattering studies of enzymes. (February 2023) - Byer, Amanda S.; Pei, Xiaokun; Patterson, Michael G.; Ando, Nozomi
Abstract: Enzyme function requires conformational changes to achieve substrate binding, domain rearrangements, and interactions with partner proteins, but these movements are difficult to observe. Small-angle X-ray scattering (SAXS) is a versatile structural technique that can probe such conformational changes under solution conditions that are physiologically relevant. Although it is generally considered a low-resolution structural technique, when used to study conformational changes as a function of time, ligand binding, or protein interactions, SAXS can provide rich insight into enzyme behavior, including subtle domain movements. In this perspective, we highlight recent uses of SAXS to probe structural enzyme changes upon ligand and partner-protein binding and discuss tools for signal deconvolution of complex protein solutions. Graphical abstract: Image 1